Herbaria century record of increasing eutrophication in Spanish terrestrial ecosystems - Josep Peñuelas; Iolanda Filella (Global Change Biology, 2001)
Summary Additional biological evidence is presented for the alteration of biogeochemical cycles by human activities. The leaf δ 15 N and the concentrations of nutrients in herbarium specimens of 24 species of vascular plants and 3 species of bryophytes collected in northern and eastern regions of Spain have substantially changed throughout the XX century. In the second half of the century, when anthropogenic nitrogen fixation and mobilization started to increase rapidly, leaf δ 15 N values started to decrease strongly, indicating that additional anthropogenic nitrogen is being retained in Spanish terrestrial ecosystems. The concentration of nutrients in vascular plants did not present any clear pattern, but there were increasing concentrations of N and other nutrients (P, K, and S) in the last decades in bryophytes, which are usually better biomonitors of airborne chemicals than vascular plants. Important consequences for ecosystem structure and functioning such as enhancement of the carbon sink or changes in community biodiversity and species distribution may be expected from this increase in eutrophication.

Leaf mineral concentrations of Erica arborea , Juniperus communis and Myrtus communis growing in the proximity of a natural CO 2 spring - Josep Peñuelas; Iolanda Filella; Roberto Tognetti (Global Change Biology, 2001)
Summary Leaf mineral concentrations of co‐occurring Erica arborea, Juniperus communis and Myrtus communis were measured at bimonthly intervals throughout a year in a natural CO 2 spring and in a nearby control site with similar soil chemistry in a Mediterranean environment. There were different responses to the elevated [CO 2 ] ( c . 700 μL L −1 ) of the spring site plants depending on the element and the species. In the CO 2 spring site K, Ca, Mg, Mn, Al, Fe, and Ti leaf concentrations and the ratio C/N showed significant greater values in at least one or two of the three species. Leaf S concentration were greater in all three species. Leaf concentrations of N, Sr, Co, and B were lower in at least one or two species, and those of C and Ba were lower in all the three studied species near the CO 2 spring. P, Na, Zn, Si, Cu, Ni, Cr, Pb, Mo, V and Cd leaf concentrations and the specific leaf area (SLA, measured in Myrtus communis ) did not show any consistent or significant pattern in response to the elevated [CO 2 ] of the spring site. There was a slight trend towards maximum concentrations of most of these elements during autumn–winter and minimum values during the spring season, especially in Myrtus communis . Multivariate principal component analyses based on the leaf elemental concentrations clearly differentiated the two sites and the three species. Lower concentrations at the spring site were not the result of a dilution effect by increased structural or nonstructural carbon. In contrast to most experimental studies of CO 2 enrichment, mainly conducted for short periods, several of these elements had greater concentrations in the CO 2 spring site. Nutrient acclimation and possible causes including decreased nutrient export, increased nutrient uptake capacity, photosynthetic down‐regulation, Mediterranean water stress, and higher H 2 S concentration in the spring site are discussed.